High-strength high-plasticity corrosion-resistant double-phase titanium alloy material and preparation method thereof

By Fe-O microalloying and optimizing the forging process, the microstructure of titanium alloy is refined, which solves the problem of poor matching between strength and plasticity of traditional titanium alloys, and realizes high-strength, high-plasticity and corrosion-resistant titanium alloy materials suitable for extreme environments.

CN120719174APending Publication Date: 2025-09-30NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510924559.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Traditional titanium alloys have problems with difficult-to-control, complex and poor matching of strength and plasticity, making it difficult to meet the high load and deformation resistance requirements under extreme working conditions.

Method used

Through Fe-O microalloying, the size of the secondary αs phase is refined and the spheroidization degree of the equiaxed αp phase is improved. Combined with the forging process of the β single-phase region and the α+β dual-phase region, the dual-phase structure is optimized to achieve a match between high strength and high plasticity.

Benefits of technology

It significantly improves the strength of titanium alloy without reducing its plasticity, enhances its stability and corrosion resistance in extreme environments, and provides a low-cost application solution for high-end fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120719174A_ABST
    Figure CN120719174A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength, high-plasticity and corrosion-resistant double-phase titanium alloy material. The titanium alloy material comprises the following components in percentage by mass: 5.2-6.9% of Al, 3.1-4.7% of V, 0.3-0.8% of Fe, 0.06-0.15% of 0 and the balance of titanium. The balance is Ti and inevitable impurities; the microscopic structure of the titanium alloy material comprises a primary alpha p phase and a beta t phase, the primary alpha p phase comprises a lath-shaped alpha p phase and an equiaxial alpha p phase, and the beta t phase comprises a lamellar secondary alpha s phase separated out in the beta t phase; the size of a secondary alpha s phase is refined through Fe-O microalloying, meanwhile, the spheroidizing degree of an equiaxial alpha p phase is improved, and double-phase structure optimization is achieved. Through Fe-O double-element microalloying synergistic strength and accurate regulation and control of an alpha p-alpha s double-phase structure, the strength of the titanium alloy is improved under the condition that plasticity is not reduced, high-strength and high-plasticity matching of the titanium alloy is achieved, meanwhile, excellent stability is kept in an extreme environment, and the service life of the titanium alloy is prolonged. And a low-cost novel titanium alloy material solution is provided for the high-end fields of aerospace, ocean engineering and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of titanium alloys, and in particular to a high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material and a preparation method thereof. Background Art

[0002] Titanium alloy has the advantages of high specific strength, low density and excellent corrosion resistance. These characteristics determine its broad application prospects in oil drilling, shipbuilding, pipeline systems and aerospace industries. Its high strength can replace steel drill pipes to extend the extension capacity of three-dimensional horizontal wells and large-reach wells, reduce the failure of drill pipes and drive systems, and its corrosion resistance can increase the water depth of the platform and avoid seawater corrosion on the water-resistant pipe, making it an indispensable material for equipment in extreme environments.

[0003] The plasticity of titanium alloys is a key factor affecting the reliability, safety, and service life of equipment. Therefore, the plasticity of titanium alloys is also important for industries such as oil drilling and shipping where extreme conditions prevail. However, traditional titanium alloys (such as TC4) follow the "strength-plasticity inversion" law and are unable to meet the high load and deformation resistance requirements under extreme working conditions. In recent years, through refined organizational design, composition innovation, and process innovation, academia and industry have made breakthrough progress in the field of strength-plastic matching.

[0004] For example, during the β forging process, the TC6 titanium alloy is heated in a step-by-step manner, the holding time of the alloy above the phase transition point is shortened and fully heated through, and the holding temperature above the phase transition point is reasonably selected to avoid grain growth caused by excessively high holding temperatures or excessively long holding times, thereby achieving uniform grain refinement of the alloy. During the forming forging process, the lamellar α phase morphology in the basketweave structure is regulated by controlling the amount of billet drawing deformation, thereby achieving a reasonable match between strength and toughness. During the heat treatment process, by controlling the air cooling rate after the first heat treatment, the amount of metastable phase formed in the alloy is controlled, and then the amount of strengthening phase precipitated during the second low-temperature holding is controlled, thereby improving the plasticity of the alloy. For another example, the TC4 titanium alloy is prepared by combining multi-pass large deformation forging and radial forging to produce titanium alloy bars with micron-scale and micro-nanoscale mixed crystal structures, achieving the effect of increasing the strength of the titanium alloy without reducing the plasticity.

[0005] Although these methods can improve the strength-plastic matching of titanium alloys, they have the problems of complex preparation process, difficult control, imprecise control, and still poor strength-plastic matching.

[0006] Prior art literature:

[0007] Chinese Patent: CN117505749A

[0008] Chinese Patent: CN117960970A Summary of the Invention

[0009] The present invention aims to provide a high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material and its preparation method in view of the shortcomings of the prior art, by Fe-O dual-element microalloying synergistic strength, and α p- α s The precise control of the dual-phase structure improves the strength of titanium alloy without reducing plasticity, achieving a match between high strength and high plasticity of titanium alloy, while maintaining excellent stability in extreme environments, providing a low-cost new titanium alloy material solution for high-end fields such as aerospace and marine engineering.

[0010] According to a first aspect of the present invention, a high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material is provided, wherein the composition of the titanium alloy material comprises, by mass percentage, Al: 5.2-6.9%, V: 3.1-4.7%, Fe: 0.3-0.8%, O: 0.06-0.15%; the balance is Ti and unavoidable impurities;

[0011] Wherein, the microstructure of the titanium alloy material includes primary α p Phase and β t Phase, the primary α p Phases include lamellar α p Equal and equal axes α p Phase, the β t Phase included in β t The lamellar secondary α s Mutually;

[0012] Refinement of secondary α by Fe-O microalloying s phase size, while increasing the equiaxed α p The spheroidization degree of the phase is improved to achieve the optimization of the two-phase structure.

[0013] As an optional embodiment, the primary α p The phase accounts for 30% to 60% of the volume of the α+β phase.

[0014] As an optional embodiment, the isometric α p Phase occupancy of the newborn α p 55% to 80% of the phase volume.

[0015] As an optional embodiment, the isometric α p The grain size of the phase is 4 to 6 μm.

[0016] As an optional embodiment, the secondary α s The grain size of the phase is 3 to 4 μm.

[0017] According to a second aspect of the present invention, a method for preparing the aforementioned high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material is provided, comprising the following steps:

[0018] According to the composition design of the target product titanium alloy material, the corresponding materials are weighed and smelted to obtain an alloy ingot;

[0019] The alloy ingot is first subjected to cutting processing, and then subjected to a five-fire forging process, with the final forging temperature in the dual-phase region to obtain a forging blank; wherein, the first three-fire forging is carried out in the β single-phase region, and then the second-fire final forging is carried out in the α+β dual-phase region;

[0020] The forging blank is subjected to a solution aging treatment to obtain the desired high-strength, high-plasticity, and corrosion-resistant dual-phase titanium alloy material.

[0021] As an optional embodiment, the forging temperature of the β single phase region forging is T β Above 30 ~ 70 ℃, the forging temperature of the α + β dual phase region forging is T β Below 30~100℃.

[0022] As an optional embodiment, the conditions for the solution treatment include: a heating rate of 8 to 10° C. / min, a holding temperature of 900 to 930° C., and a holding time of 1 to 1.5 h.

[0023] As an optional embodiment, the conditions for aging treatment include: a holding temperature of 530 to 560° C. and a holding time of 3.5 to 4 hours.

[0024] According to a third aspect of the present invention, there is provided a titanium alloy component manufactured using the aforementioned high-strength, high-plasticity, and corrosion-resistant dual-phase titanium alloy material.

[0025] From the above technical solutions of the present invention, it can be seen that the high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material proposed by the present invention uses aluminum as a stabilizing α-phase element, vanadium as a stabilizing β-phase element, and the addition of trace iron elements leads to β-phase t The redistribution of the composition between V and Fe in the phase promotes the deformation and vibration of the lattice and refines the α s The increase in yield strength and tensile strength is also due to the kinked β+α layer microstructure at the crack tip and the improved fracture surface due to Fe addition. The expanded plastic zone, redirected crack propagation and more uniformly distributed dimples also help to achieve the optimal ratio of strength and plasticity. The addition of O significantly affects the morphology of the primary α phase during the solution aging process, promoting the formation of the primary α phase in the lath. p Opposite equiaxed primary α p Phase transformation; in this way, the dual-phase structure optimization is achieved through Fe-O microalloying, which enables the strength of titanium alloy to be improved without reducing plasticity, achieving the matching of high strength and high plasticity of titanium alloy, while still having good corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 1 and 2 are scanning electron microscope images of samples in the examples of the present invention; wherein, a is the sample of Example 1; b is the sample of Example 2; c is the sample of Example 3; d is the sample of Example 4; e is the sample of Example 5; and f is the sample of Example 6.

[0027] Figure 2 It is the tensile stress-strain curve of the sample in Example 5.

[0028] Figure 3 This is a macro-micro scanning image of the tensile fracture of the sample of Example 5 at room temperature; wherein a is a macro image; b is a micro image.

[0029] Figure 4 This is a macro-micro scanning image of the tensile fracture of the sample of Example 6 at room temperature; wherein a is a macro image; b is a micro image.

[0030] Figure 5 These are macro-micro scanning images of the tensile fractures of the samples of Example 1, Example 3, and Example 4 under room temperature; wherein, a is the macro image of the sample of Example 1, and a1 is the micro image of the sample of Example 1; b is the macro image of the sample of Example 3, and b1 is the micro image of the sample of Example 3; c is the macro image of the sample of Example 4, and c1 is the micro image of the sample of Example 4.

[0031] Figure 6 These are the potentiodynamic polarization curves of multiple groups of samples after different heat treatments.

[0032] Figure 7 These are the electrochemical impedance spectra of multiple groups of samples after different heat treatments.

[0033] Figure 8 It is the Bode plot of multiple groups of samples after different heat treatments. DETAILED DESCRIPTION

[0034] In order to better understand the technical content of the present invention, specific embodiments are given and described below with reference to the accompanying drawings.

[0035] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which a number of illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to be comprehensive. It should be understood that the various concepts and embodiments described above, as well as those described in more detail below, can be implemented in any of a number of ways.

[0036] The present invention adds trace amounts of Fe to redistribute the β-phase components, refines the structure through lattice dynamics effects, and regulates crack propagation. The addition of trace amounts of O elements causes elastic interaction and Zener pinning to promote the transformation of the α-phase morphology from laths to equiaxed ones. The two synergistically optimize the deformation mechanism, form multi-slip system initiation and interface coordinated deformation, and optimize the fracture behavior, resulting in crack tip kinking and path tortuosity. The size and morphology of the α-phase in the dual-phase structure are regulated by Fe-O microalloying to achieve dual-phase structure optimization, forming a linkage relationship of "element regulation-structure optimization-performance improvement", and ultimately improving strength without reducing plasticity, ensuring high strength while achieving high plasticity, and providing new ideas for the application of titanium alloys under extreme working conditions.

[0037] In an exemplary embodiment of the present invention, a high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material is provided. The composition of the titanium alloy material includes, by mass percentage, Al: 5.2-6.9%, V: 3.1-4.7%, Fe: 0.3-0.8%, O: 0.06-0.15%; the balance is Ti and unavoidable impurities;

[0038] The obtained titanium alloy material microstructure includes primary α p Phase and β t phase (α+β phase), primary α p Phases include lamellar α p Equal and equal axes α p Phase, β t Phase included in β t The lamellar secondary α s Mutually;

[0039] Refinement of secondary α by Fe-O microalloying s phase size, while increasing the equiaxed α p The spheroidization degree of the phase is improved to achieve the optimization of the two-phase structure.

[0040] In one of the optional examples, the nascent α p The phase occupies 30% to 60% of the volume of the α+β phase, and particularly preferably 30% to 40%.

[0041] In one of the alternative examples, the isometric α p Phase occupancy of the newborn α p 55% to 80% of the phase volume, particularly preferably 70% to 80%.

[0042] In one of the alternative examples, the isometric α p The grain size of the phase is 4 to 6 μm, particularly preferably 4.3 to 5 μm.

[0043] In one of the optional examples, the secondary α sThe grain size of the phase is 3 to 4 μm.

[0044] In one optional example, the unavoidable impurities include, by mass percentage: H: ≤0.005%, N: ≤0.015%, C: ≤0.02%.

[0045] In another exemplary embodiment of the present invention, a method for preparing the aforementioned high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material is provided, comprising the following steps:

[0046] According to the composition design of the target product titanium alloy material, the corresponding materials are weighed and smelted to obtain an alloy ingot;

[0047] The alloy ingot is first cut and then forged by β forging and five-fire forging process, with the final forging temperature in the dual-phase region to obtain a forged billet; wherein, three-fire forging is first performed in the β single-phase region, and then two-fire final forging is performed in the α+β dual-phase region;

[0048] The forging blank is subjected to a solution aging treatment to obtain the desired high-strength, high-plasticity, and corrosion-resistant dual-phase titanium alloy material.

[0049] In one of the optional examples, the forging temperature of the β single phase region forging is T β Above 30~70℃.

[0050] In one of the optional examples, the forging temperature of the α+β dual phase region forging is T β Below 30~100℃.

[0051] It is understandable that after obtaining the alloy ingot, the phase transition temperature of the alloy can be measured by metallographic method, that is, T β , and then determine the subsequent forging temperature.

[0052] In one optional example, the conditions for the solution treatment include: a heating rate of 8 to 10° C. / min, a holding temperature of 870 to 930° C., and a holding time of 1 to 1.5 h.

[0053] In one optional example, the aging treatment conditions include: a holding temperature of 530-560° C. and a holding time of 3.5-4 hours.

[0054] Below, we provide a specific method for preparing the aforementioned high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material, comprising the following specific steps:

[0055] Step 1, composition optimization: optimize the alloy composition, which includes Al: 5.2-6.9%, V: 3.1-4.7%, Fe: 0.3-0.8%, O: 0.06-0.15% and the balance Ti by mass percentage, and perform three smelting in a vacuum consumable arc furnace to obtain a titanium alloy ingot. The alloy phase transition temperature (T β ).

[0056] The smelting process specifically includes the following steps:

[0057] After weighing, mixing, pressing electrodes and welding, the materials are melted once in a vacuum consumable arc furnace to obtain an ingot;

[0058] After welding the primary ingot, the ingot is subjected to secondary smelting in a vacuum consumable arc furnace to obtain a secondary ingot;

[0059] After welding the secondary ingot, the ingot is smelted three times in a vacuum consumable arc furnace to obtain a third ingot; after removing the riser and peeling the third ingot, the alloy ingot is obtained;

[0060] Among them, the parameter settings for the first melting are as follows: melting current is 3-5KA, arc stabilization current is 0.3-3A, and melting voltage is 29-33V; the parameter settings for the second melting are as follows: melting current is 1-3KA, arc stabilization current is 3.5-5.5A, and melting voltage is 29-33V; the parameter settings for the third melting are as follows: melting current is 1-3KA, arc stabilization current is 1-6A, and melting voltage is 25-30V.

[0061] Step 2, forging optimization: the alloy ingot is first cut and then subjected to five-fire forging process. The final forging temperature is in the dual-phase region to obtain a forging blank. Forging with a forging machine can break up large dendritic grains, change the microstructure of the alloy, and significantly improve the mechanical properties of the alloy. Among them, the bar forging adopts β forging to open the blank, and three-fire β single-phase forging (T β Above 30~70℃), two-time dual phase forging (T β The temperature is below 30-100℃), and the deformation of each forging is about 40%. After each forging, it is air-cooled to room temperature to ensure that the oxide scale is removed and the cracks are polished when peeling.

[0062] Step 3, heat treatment optimization: the forging blank obtained in step 2 is subjected to solution aging treatment after vacuum sealing treatment, the solution temperature is 870-930℃, the holding time is 1-1.5h, the holding temperature of aging treatment is 530-560℃, the holding time of aging treatment is 4-4.5h, so that the microstructure is transformed into lamellar αp, equiaxed αp and fine lamellar primary αs phase, and the primary α p Phase accounts for 30% to 60% of the α+β phase, and the equiaxed α p Phase occupancy of the newborn α p55% to 80% of the phase, equiaxed α p The grain size of the phase is maintained at 4 to 6 μm, resulting in a high-strength and high-corrosion-resistant titanium alloy.

[0063] The preparation process of the present invention is simple, easy to control, highly efficient, low-cost, and can precisely regulate the microstructure. The obtained titanium alloy has a tensile strength of 1022-1033 MPa, an elongation after fracture maintained at 14.5%-16%, a high degree of strength-plastic matching, excellent comprehensive mechanical properties, and excellent corrosion resistance.

[0064] In other exemplary embodiments of the present invention, a titanium alloy component is provided which is made of the aforementioned high-strength, high-plasticity, and corrosion-resistant dual-phase titanium alloy material. The titanium alloy component has the characteristics of high strength, high plasticity, and corrosion resistance, and can meet the requirements of use under extreme working conditions.

[0065] For better understanding, the present invention is further described below with reference to several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.

[0066] Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.

[0067] Example 1

[0068] The composition of the ingot is, by mass percentage, Al: 6.08%, V: 4.17%, Fe: 0.56%, O: 0.086% and the balance Ti.

[0069] (1) Electrode preparation: The raw materials of grade 0 titanium sponge, aluminum vanadium alloy, aluminum bean, titanium iron alloy and titanium dioxide are pressed into consumable electrodes by a hydraulic press and then plasma welded to obtain electrodes.

[0070] (2) Melting the consumable electrode in a vacuum consumable arc furnace: melting once under the conditions of a melting current of 3-5KA, a stabilizing arc current of 0.3-3A, and a melting voltage of 29-33V to obtain an ingot;

[0071] After welding the primary ingot, the ingot is passed through a vacuum consumable arc furnace and subjected to secondary melting under the conditions of a melting current of 1-3KA, a stable arc current of 3.5-5.5A, and a melting voltage of 29-33V to obtain a secondary ingot;

[0072] After welding the secondary ingot, the ingot is passed through a vacuum consumable arc furnace and smelted for a third time under the conditions of a melting current of 1-3KA, a stabilizing arc current of 1-6A, and a melting voltage of 25-30V to obtain a third ingot;

[0073] After removing the riser and peeling the ingots three times, the alloy ingot was obtained. The alloy phase transition point temperature (Tβ) was measured by metallographic method to be 950℃±5℃.

[0074] (3) The alloy ingot is first cut and then forged in the β single phase region for three times at 1010, 1010, and 1010°C, and then forged in the dual phase region for two times at 930 and 910°C. The deformation of each forging is about 40%. After each forging, the forging blank is air-cooled to room temperature to obtain a forging blank.

[0075] Example 2

[0076] The composition of the ingot is, by mass percentage, Al: 6.08%, V: 4.17%, Fe: 0.56%, O: 0.086% and the balance Ti.

[0077] A forging blank was obtained according to steps (1), (2) and (3) of Example 1.

[0078] (4) The forging blank is cut, and the cut sample is vacuum sealed to avoid oxidation of the sample during the solution aging process. Then, the sample is placed in a muffle furnace for solution aging treatment by heating with the furnace. Among them, the heating rate of the solution aging process is 10℃ / min, the solution temperature is 830℃, and the temperature is kept for 1.5h. The sample is air-cooled and aged after cooling to room temperature. The aging temperature is 550℃ and the temperature is kept for 4h. The cooling method is air-cooling to obtain the sample.

[0079] Example 3

[0080] The composition of the ingot is, by mass percentage, Al: 6.08%, V: 4.17%, Fe: 0.56%, O: 0.086% and the balance Ti.

[0081] A forging blank was obtained according to steps (1), (2) and (3) of Example 1.

[0082] (4) The forging blank is cut, and the cut sample is vacuum sealed to avoid oxidation of the sample during the solution aging process. Then, the sample is placed in a muffle furnace for solution aging treatment by heating with the furnace. Among them, the heating rate of the solution aging process is 10℃ / min, the solution temperature is 870℃, and the temperature is kept for 1.5h. The sample is air-cooled and cooled to room temperature before aging. The aging temperature is 550℃ and the temperature is kept for 4h. The cooling method is air-cooling to obtain the sample.

[0083] Example 4

[0084] The composition of the ingot is, by mass percentage, Al: 6.08%, V: 4.17%, Fe: 0.56%, O: 0.086% and the balance Ti.

[0085] A forging blank was obtained according to steps (1), (2) and (3) of Example 1.

[0086] (4) The forging blank is cut, and the cut sample is vacuum sealed to avoid oxidation of the sample during the solution aging process. Then, the sample is placed in a muffle furnace for solution aging treatment by heating with the furnace. The heating rate of the solution aging process is 10℃ / min, the solution temperature is 900℃, and the temperature is kept for 1.5h. The sample is air-cooled and aged after cooling to room temperature. The aging temperature is 550℃ and the temperature is kept for 4h. The cooling method is air-cooling to obtain the sample.

[0087] Example 5

[0088] The composition of the ingot is, by mass percentage, Al: 6.08%, V: 4.17%, Fe: 0.56%, O: 0.086% and the balance Ti.

[0089] A forging blank was obtained according to steps (1), (2) and (3) of Example 1.

[0090] (4) The forging blank is cut, and the cut sample is vacuum sealed to avoid oxidation of the sample during the solution aging process. Then, the sample is placed in a muffle furnace for solution aging treatment by heating with the furnace. Among them, the heating rate of the solution aging process is 10℃ / min, the solution temperature is 930℃, and the temperature is kept for 1.5h. The sample is air-cooled and cooled to room temperature before aging. The aging temperature is 550℃ and the temperature is kept for 4h. The cooling method is air-cooling to obtain the sample.

[0091] Example 6

[0092] The composition of the ingot is, by mass percentage, Al: 6.08%, V: 4.17%, Fe: 0.56%, O: 0.086% and the balance Ti.

[0093] A forging blank was obtained according to steps (1), (2) and (3) of Example 1.

[0094] (4) The forging blank is cut, and the cut sample is vacuum sealed to avoid oxidation of the sample during the solution aging process. Then, the sample is placed in a muffle furnace for solution aging treatment by heating with the furnace. Among them, the heating rate of the solution aging process is 10℃ / min, the solution temperature is 940℃, and the temperature is kept for 1.5h. The sample is air-cooled and cooled to room temperature before aging. The aging temperature is 550℃ and the temperature is kept for 4h. The cooling method is air-cooling to obtain the sample.

[0095] Comparative Example 1

[0096] The composition of the ingot is, by mass percentage, Al: 6.01%, V: 4.05% and the balance Ti.

[0097] An alloy ingot was obtained according to steps (1) and (2) of Example 1, and the alloy phase transition temperature (Tβ) was measured by metallographic method to be 970°C±5°C.

[0098] (3) The alloy ingot was first cut, and then forged in the β single phase region for three times at 1010, 1010, and 1010 °C, and then forged in the dual phase region for two times at 930 and 910 °C. The deformation of each forging was about 40%. After each forging, the ingot was air-cooled to room temperature to obtain a sample.

[0099] Comparative Example 2

[0100] The composition of the ingot is, by mass percentage, Al: 6.01%, V: 4.05% and the balance Ti.

[0101] A forging blank was obtained according to steps (1), (2) and (3) of Comparative Example 1.

[0102] (4) The forging blank is cut, and the cut sample is vacuum sealed to avoid oxidation of the sample during the solution aging process. Then, the sample is placed in a muffle furnace for solution aging treatment by heating with the furnace. The heating rate of the solution aging process is 10℃ / min, the solution temperature is 900℃, and the temperature is kept for 1.5h. The sample is air-cooled and aged after cooling to room temperature. The aging temperature is 550℃ and the temperature is kept for 4h. The cooling method is air-cooling to obtain the sample.

[0103] Comparative Example 3

[0104] The difference from Comparative Example 2 is that the solution temperature is 930°C to obtain a sample.

[0105] Comparative Example 4

[0106] The difference from Comparative Example 2 is that the solution temperature is 940°C to obtain a sample.

[0107] SEM testing

[0108] The samples of Examples 1-6 were subjected to SEM testing, and the results were as follows: Figure 1 shown.

[0109] It can be seen from the figure that when the solution temperature is low, after solution treatment at 830℃ and 870℃, a large number of lamellar α p tissue, in which the primary α p The content is 60%-70%, equiaxed α pThe content accounts for about the total primary α p 20% of.

[0110] When the solution temperature is 830℃, the primary α p Phase content is about 76%, at this time, the primary α p The phase is mainly composed of lamellar α p Composition, lath-shaped α p The grain size is 7.1-7.3μm; as the temperature increases to 870℃, the primary α p Phase content is reduced to 70%, at this time, the primary α p The phase is still mainly composed of lamellar α p Composition, lath-shaped α p The grain size is about 6.3-6.7μm, equiaxed α p The content accounts for about α p 30% of the content.

[0111] After solution aging heat treatment at 900℃, the primary α p Phase presents regular lamellar α p , isometric α p and lamellar α s , where the primary α p The content is about 58%. At this time, the primary α p Lath-like α p and isometric α p Composition, isometric α p The grain size is 5.5-5.9μm, and the equiaxed αp content accounts for about α p The content is 55%; as the solution temperature rises to 930℃, the lamellar α p The spheroidization rate also increases, among which the primary α p The content is reduced to 30%, mainly composed of equiaxed α p Phase composition, isometric α p The content accounts for about the total primary α p Content 80%, equiaxed α p The grain size is about 4.3-5.0μm, α s The grain size of the phase is 3 to 4 μm.

[0112] When the solution temperature rises to 940℃, the content of lamellar αs increases significantly, but the lamellar α p , isometric α p Phase content decreases sharply, primary α p The phase content shows a trend of gradually decreasing with the increase of solid solution temperature. p The grain size shows a trend of increasing first and then decreasing, among which the primary α p The content dropped sharply to 12%, the equiaxed α pThe grain size reaches its minimum value of about 4 μm at the solution temperature of 940 °C.

[0113] Mechanical properties testing

[0114] At room temperature, referring to GB / T228.1-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method" standard, an AGS-X electronic universal testing machine was used to carry out uniaxial tensile tests to obtain the tensile strength (Rm), yield strength (Rp0.2), elongation (A) and shrinkage after fracture (Z). The results are shown in Table 1.

[0115] Table 1

[0116]

[0117] As can be seen from the above table, compared with the comparative examples, the elongation and cross-sectional shrinkage of Examples 1, 2, 3, 4, 5 and 6 are generally higher, among which the elongation of Examples 4 and 5 is better improved, by 5%. Compared with Examples 2, 3, 4 and 6, Example 5 has higher tensile strength, yield strength and elongation.

[0118] Combining SEM testing with Figure 2 The tensile mechanical properties curve shows that under the alloy composition conditions of the present invention, the primary α p Phase content is 30% to 60%, the spheroidized primary α p The content is between 55% and 80%, and the average grain size is between 4 and 6 μm. s The average grain size of the phase is between 3 and 4 μm, and the α s The combination improves strength without reducing plasticity, ensures high strength while achieving high plasticity, and realizes a high match between alloy strength and plasticity, with excellent comprehensive mechanical properties.

[0119] Tensile fracture analysis

[0120] like Figure 3 As shown in the figure, the fracture of the sample of Example 5 presents a typical "bowl-shaped" fracture morphology, with a plastic fracture zone with dense dimples in the center and a slight shear lip on the edge, showing an outward-extending dimple zone, which may start from certain defects on the edge (a depression can be seen in the lower right corner), but the overall feature is a typical ductile fracture, which belongs to a ductility-dominated fracture; a large number of equiaxially distributed deep dimples with clear edges and full morphology, and small micropores can be seen inside some dimples; this indicates that there is an obvious micropore aggregation mechanism in the fracture process, and the pores initiate in the weak area of ​​the interface and then connect into dimples, showing good plasticity.

[0121] Depend on Figure 4It can be seen that the fracture of the sample of Example 6 presents a cup-cone fracture feature, indicating that the material has undergone plastic deformation during the stretching process, and the fracture mode is still mainly ductile fracture. The crack initiation zone is located in the central area and then expands to the outside, which may be related to the internal microscopic defects of the material or the organizational state after heat treatment; the shear lip is relatively obvious, indicating that the material has undergone a certain amount of plastic deformation before fracture and has not undergone complete brittle fracture; the fracture surface is still dominated by dimples, but compared with the previous specimens, the dimple size is slightly reduced, indicating that the plasticity is slightly reduced; the local appearance of tearing edges indicates that there may be stress concentration in the local area, resulting in faster crack expansion.

[0122] The titanium alloy of Example 5 has more spheroidized primary α p Phase and fine layer α s Phase, these two organizations preliminarily determine that the alloy has a good strength-ductility ratio; at the same time, the spheroidized primary α p The crack deflects during the tensile process, and the crack bends when it crosses the grain, causing the α s The orientation of the grains tends to the direction of crack propagation, and the crack becomes along the α s / β t Phase boundary propagation, this phenomenon can alleviate the crack in the cross-lamellar α s The stress concentration occurs when the grains are formed, so that the alloy dissipates more tensile energy. p The phase content drops sharply, the plasticity is greatly reduced, and the deformation coordination ability of the organization is weakened.

[0123] Figure 5 The following are SEM images of the tensile fracture morphology of the samples of Comparative Examples 1, 3, and 4, and Figures (a) and (a1) are scanned images of the fracture morphology of Comparative Example 1. As can be seen from the figure, the fracture presents a typical cup-cone fracture, indicating that the sample has undergone a certain amount of plastic deformation during the tensile process, but the degree of plastic deformation is slightly lower than that of the previous group. The central area is rough, and some holes or inclusions can be seen, which may be the starting point of crack initiation and cause crack expansion with loading. The shear lip is not obvious, which may indicate that the plastic deformation ability is relatively weak. Holes can still be seen in some areas, which may be related to the pores or inclusions remaining inside the material. These defects may cause stress concentration during the tensile process.

[0124] Figures (b) and (b1) are scanned images of the fracture morphology of Comparative Example 3. As can be seen from the figure, the fracture presents a cup-cone fracture feature, indicating that the sample fractured after undergoing a certain amount of plastic deformation, and still exhibited certain toughness characteristics. The crack initiation zone may be concentrated in the central area and expand outward, which may be related to microscopic defects or structural inhomogeneities inside the material. The shear lip is not obvious, indicating that the toughness deformation ability may have decreased during the fracture process. The fracture surface is mainly composed of dimples, indicating that the sample is still mainly ductile fracture. Some hole defects can still be seen on the fracture, which may come from pores or inclusions remaining inside the material. Compared with the fracture morphology of Comparative Example 1, the dimple distribution of Comparative Example 3 is obviously more uniform, and the stress concentration is not obvious.

[0125] Figures (c) and (c1) are the fracture morphology scans of Comparative Example 4. In Comparative Example 4, since the solid solution temperature is close to the phase transition point, the primary α p The content dropped sharply, and the secondary α s The content increases. Compared with Figures (b) and (b1), larger hole-like defects appear in local areas of its surface, which may be related to inclusions, pores or microcracks in the material. The crack initiation area is relatively concentrated and accompanied by local tearing edges, indicating that the crack may have rapidly extended in the high stress area, and brittle fracture characteristics may have appeared in some areas. The edge of the fracture is relatively smooth, while the central area shows more fracture dimples, which may indicate that after the material undergoes initial plastic deformation during the tensile process, the crack rapidly extends and eventually breaks, but the dimple size distribution is uneven, which may be related to the inhomogeneity of the structure after heat treatment. The presence of locally large holes may be due to the residual pores or inclusions in the material during the casting process, which become the source of crack initiation during the tensile process, causing premature fracture. The visible fracture surface and tearing edges indicate that the material may have undergone a mixed ductile-brittle fracture mechanism locally.

[0126] By analyzing the fracture morphology of the examples and comparing them with the comparative examples, it can be further proved that under the conditions of the alloy composition of the present invention, the primary α p The phase content is between 30% and 60%, the primary αp content of spheroidization is between 55% and 80%, and the average grain size is between 4 and 6 μm. s The average grain size of the phase is between 3 and 4 μm, which can achieve a high match between the strength and plasticity of the alloy.

[0127] Electrochemical corrosion testing

[0128] Electrochemical corrosion tests were conducted on Examples 2, 3, 4, 5, and 6 with 780°C / 1.5h / AC, 800°C / 1.5h / AC, and 1010°C / 1.5h / AC+720°C / 4h / AC (the difference between the preparation of the sample of 780°C / 1.5h / AC and that of Example 2 is that the solution temperature is 780°C; the difference between the preparation of the sample of 800°C / 1.5h / AC and that of Example 2 is that the solution temperature is 800°C; the difference between the preparation of the sample of 1010°C / 1.5h / AC+720°C / 4h / AC and that of Example 2 is that the solution temperature is 1010°C and the aging temperature is 720°C). The results are as follows: Figure 6-8 shown.

[0129] The electrochemical impedance spectroscopy of the samples after different heat treatments in 3.5wt% NaCl solution is shown in Figure 2. Figure 6 As shown in the figure, since impedance spectroscopy is an electrochemical method that reflects the corrosion resistance of a material by testing the impedance value of the material surface, the shape of the impedance spectrum is related to the passivation film on the material surface. The corrosion resistance of the alloy can be qualitatively judged from the impedance spectrum. The larger the radius of the arc in the spectrum, the greater the impedance value of the corresponding material and the better the corrosion resistance. The curve corresponding to the solution temperature of 930℃ in the figure shows the largest arc radius, indicating that it has the largest polarization resistance and the best corrosion resistance. The polarization resistance is the slope of the tangent of the polarization curve at the corrosion potential. The larger its value, the greater the resistance to the electrode reaction and the lower the corrosion rate. The radius of curvature is the smallest at 800℃, which means that it has the weakest ability to inhibit polarized electron transfer.

[0130] Electrochemical impedance spectroscopy can not only Figure 7 The Nyquist diagram can be used to reflect the corrosion resistance of the material. Figure 8 The Bode diagram shows that two different regions can be found through the relationship between the impedance mode and the frequency. In the high-frequency stage (104-105Hz), the slope of this area is close to 0 due to the response of the solution resistance. When the frequency is lower than 103Hz, the curve shows a slope of about -1, which is the response characteristic of the capacitance behavior of the passivation film on the surface of the material. In the relationship between the opposite number of the phase angle and the frequency, it can be found that a single constant phase angle is exhibited in the medium-frequency region (100-102Hz), and its phase angle is stable at about 80°. In the low-frequency stage, high-temperature annealing at 930°C has the highest phase angle value and the absolute value of impedance, indicating that it has the best corrosion resistance.

[0131] It can be proved from the above that the curve corresponding to the solution temperature of 930℃ shows the largest arc radius, indicating that it has the largest polarization resistance and the best corrosion resistance; polarization resistance is the slope of the tangent of the polarization curve at the corrosion potential. The larger its value, the greater the resistance to the electrode reaction, the smaller the corrosion rate, and the best corrosion resistance.

[0132] Therefore, it can be seen from the above tests that the present invention achieves dual-phase structure optimization through Fe-O microalloying, so that the strength of the titanium alloy is improved without reducing the plasticity, achieving the matching of high strength and high plasticity of the titanium alloy, while still having good corrosion resistance.

[0133] While the present invention has been disclosed above with reference to preferred embodiments, this is not intended to limit the present invention. Persons skilled in the art will readily appreciate that various modifications and variations can be made without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the claims.

Claims

1. A high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material, characterized in that: The components of the titanium alloy material include, by mass percentage, Al: 5.2-6.9%, V: 3.1-4.7%, Fe: 0.3-0.8%, O: 0.06-0.15%; the balance is Ti and unavoidable impurities; Wherein, the microstructure of the titanium alloy material includes primary α p Phase and β t Phase, the primary α p Phases include lamellar α p Equal and equal axes α p Phase, the β t Phase included in β t The lamellar secondary α s Mutually; Refinement of secondary α by Fe-O microalloying s phase size, while increasing the equiaxed α p The spheroidization degree of the phase is improved to achieve the optimization of the two-phase structure.

2. The high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material according to claim 1, characterized in that: The nascent α p The phase accounts for 30% to 60% of the volume of the α+β phase.

3. The high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material according to claim 1, characterized in that: The isometric α p Phase occupancy of the newborn α p 55% to 80% of the phase volume.

4. The high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material according to claim 1, characterized in that: The isometric α p The grain size of the phase is 4 to 6 μm.

5. The high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material according to claim 1, characterized in that: The secondary α s The grain size of the phase is 3 to 4 μm.

6. A method for preparing the high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material according to any one of claims 1 to 5, characterized in that: The following steps are involved: According to the composition design of the target product titanium alloy material, the corresponding materials are weighed and smelted to obtain an alloy ingot; The alloy ingot is first subjected to cutting processing, and then subjected to a five-fire forging process, with the final forging temperature in the dual-phase region to obtain a forging blank; wherein, the first three-fire forging is carried out in the β single-phase region, and then the second-fire final forging is carried out in the α+β dual-phase region; The forging blank is subjected to a solution aging treatment to obtain the desired high-strength, high-plasticity, and corrosion-resistant dual-phase titanium alloy material.

7. The method for preparing a high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material according to claim 6, characterized in that: The forging temperature of the β single-phase region forging is 30 to 70° C. above Tβ, and the forging temperature of the α+β dual-phase region forging is 30 to 100° C. below Tβ.

8. The method for preparing a high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material according to claim 6, characterized in that: The conditions of the solution treatment include: a heating rate of 8 to 10° C. / min, a holding temperature of 900 to 930° C., and a holding time of 1 to 1.5 h.

9. The method for preparing a high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material according to claim 6, characterized in that: The conditions of the aging treatment include: a holding temperature of 530 to 560° C. and a holding time of 3.5 to 4 hours.

10. A titanium alloy component made of the high-strength, high-plasticity, corrosion-resistant dual-phase titanium alloy material according to any one of claims 1 to 5.